Strategi Komunikasi Bumdes Dalam Memberdayakan Pelaku UMKM Di Desa Malanggaten - Suwanto Suwanto; Romi Iriandi Putra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Empowering Micro, Small, and Medium Enterprises (UMKM) is a crucial step in improving the rural economy. The success of the empowerment process is heavily influenced by the communication strategies implemented by village economic institutions, including Village-Owned Enterprises (BUMDes). This study aims to describe and analyse the communication strategies employed by BUMDes to empower UMKM in Malanggaten Village. The study employed a qualitative approach with a descriptive design. Data were obtained through in-depth interviews, observation, and documentation. The informants included BUMDes directors, BUMDes supervisors, and UMKM involved in the empowerment program. Data validity was tested using source triangulation and technical triangulation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that BUMDes communication strategies are implemented by understanding UMKM needs, delivering information in a participatory manner, providing mentoring and training, and utilising face-to-face and digital communication media. The use of persuasive, familial, and locally culture-based approaches can increase UMKM ' involvement in various empowerment programs. Ongoing mentoring increases business capacity, while the use of digital media accelerates information dissemination and coordination of activities. Research findings confirm that participatory, adaptive, and community-focused communication strategies play a critical role in supporting UMKM empowerment and sustainable economic development in villages.